Fly, wild swans : my mother, myself and China - Chang, Jung, 1952- (Harper, an imprint of HarperCollinsPublishers, 2025)
In this follow-up to Chang's Wild Swans, "Deng Xiaoping opened the door of Communist China, and Jung--twenty-six years old and unstoppably curious, despite years of brainwashing--seized the propitious moment and became one of the first Chinese to leave the tightly sealed country and come to the West. [This memoir] chronicles her journey and that of her family, along with that of China, as it rose from a decrepit and isolated state to a world power challenging American dominance. During those decades, although she lives in the West, Jung's life intertwines with her native land in unexpected ways, a rare relationship made more complex because all her books are banned there. Her family story mirrors the ups and downs of China's transformation, right up to today, as it enters another watershed. Chairman Xi Jinping's attempt to return China to the anti-American Maoist past has a devastating impact on Jung's life: she is unable to go to her mother's deathbed"--